2017
DOI: 10.1016/j.disc.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Some comments on the Slater number

Abstract: Let G be a graph with degree sequence d 1 ≥ . . . ≥ d n . Slater proposed sℓ(G) = min{s : (d 1 + 1) + · · · + (d s + 1) ≥ n} as a lower bound on the domination number γ(G) of G. We show that deciding the equality of γ(G) and sℓ(G) for a given graph G is NP-complete but that one can decide efficiently whether+ 1 sℓ(G). For real numbers α and β with α ≥ max{0, β}, let G(α, β) be the class of non-null graphs G such that every non-null subgraph H of G has at most αn(H) − β many edges. Generalizing a result of Deso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The following inequality was independently proved by Gentner and Rautenbach [9], and Desormeaux and Henning [7].…”
Section: Packing-related Parameters In Treesmentioning
confidence: 99%
“…The following inequality was independently proved by Gentner and Rautenbach [9], and Desormeaux and Henning [7].…”
Section: Packing-related Parameters In Treesmentioning
confidence: 99%
“…Slater [18] showed that the domination number of a graph of order n with non-increasing degree sequence d 1 ≥ • • • ≥ d n can be bound from below by the smallest integer t such that t added to the sum of the first t terms of the above-mentioned sequence is at least n. This parameter was first called the Slater number and denoted by sℓ(G) in [6]. This parameter and its properties have been investigated in [10] and [11].…”
Section: Introductionmentioning
confidence: 99%
“…Note that for some other domination parameters, lower bounds similar to the double Slater number can be obtained. The reader can consult [1], [7] and [11] for more pieces of information about them.…”
Section: Introductionmentioning
confidence: 99%